Teologiekroniek - Teologie en Konteks: ‘n Nederlandse diskussie - Wethmar, C. J. (Verbum et ecclesia, 2000)
Theology and context: a Dutch discussion In this article an analysis is made of the lectures presented to a conference on theology between church, university and society, organised by the Netherlands School for Advanced Studies in Theology and Religion in the Dutch town Hoeven from 5 to 7 June of this year. The analysis is preceded by a brief overview of the present state of affairs regarding the provision of tertiary theological education in the Netherlands. The basic tenor of this wide ranging conference was that theology could and should develop a harmonious relationship to all the contexts in which it operates.